2018
DOI: 10.1371/journal.pone.0190273
|View full text |Cite
|
Sign up to set email alerts
|

The impact of optic nerve and related characteristics on disc area measurements derived from different imaging techniques

Abstract: PurposeOptic nerve head (ONH) assessment and its interpretation in healthy patients and those with glaucoma remains a pivotal topic specifically considering rapid advancements in imaging technologies. We undertook a large-scale, mixed cohort, comparative study to assess the correlation of optic disc measurements between different imaging modalities and investigated the impact of patient and disc associated parameters.MethodsONH sizes were obtained from one randomly selected eye of each of 209 patients using st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…28 Similarly, measurements obtained with OCT are usually lower than those obtained by stereophotography or confocal laser scanning ophthalmoscopy, with correlation coefficients between them ranging from 0.83 and 0.93. 29 This is not contradictory to obtaining good reproducibility values with a particular method, as has been pointed out in our case. Therefore, as mentioned in a previous paragraph, absolute values are of little clinical and comparative value and it has even been suggested to dispense of them and to use standardised values.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…28 Similarly, measurements obtained with OCT are usually lower than those obtained by stereophotography or confocal laser scanning ophthalmoscopy, with correlation coefficients between them ranging from 0.83 and 0.93. 29 This is not contradictory to obtaining good reproducibility values with a particular method, as has been pointed out in our case. Therefore, as mentioned in a previous paragraph, absolute values are of little clinical and comparative value and it has even been suggested to dispense of them and to use standardised values.…”
Section: Discussionsupporting
confidence: 78%
“…Similarly, measurements obtained with OCT are usually lower than those obtained by stereophotography or confocal laser scanning ophthalmoscopy, with correlation coefficients between them ranging from 0.83 and 0.93. 29 …”
Section: Discussionmentioning
confidence: 99%
“…Estimation of actual size optic disc area with Littmann’s mathematical approximations from color fundus images has < 4% bias [ 38 , 39 ] compared with a bias within 2% when disc area is measured using confocal scanning laser ophthalmoscope [ 40 ]. A good correlation is shown between these two methods despite some differences in optic disc area measurements [ 41 ]. In addition, simultaneous measurements of optic disc area by color fundus photographs and confocal scanning laser ophthalmoscope were made in 52 randomly selected eyes during the present study and no significant differences were found between the two methods [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…This was attributed in part to the manual outlining of the margin, which can be better detected in disc photographs versus disc scans [ 16 ].On the contrary, OCT tended to measure optic disc size about 10% smaller when compared to disc photographs [ 17 ]. Yapp et al (2018) compared operator-driven (stereoscopic photography and CSLT) and automatic (BMO-OCT) disc size area measuring techniques [ 18 ]. The results showed that while CSLT and disc photography showed good correlation, BMO size tended to be smaller when measured by OCT. Additionally, a slightly greater deviation tendency was noted with increasing disc size.…”
Section: Discussionmentioning
confidence: 99%